A orientação do crescimento econômico da Alemanha pela expansão das exportações: uma análise da evolução e sensibilidade das exportações do país ao comportamento da demanda externa no período 2000-2017 - Vendruscolo, Bruno Dalle Piagge (2019)
This study aims to identify to which extent - and also if - the exports of goods in Germany (Eurostat) are conditioned by the foreign demand (OECD) between 2000 and 2017. According to the applied methodology, using an Autoregressive Distributed Lag (ARDL) model and the bounds test for cointegration, the estimated coefficients indicate, for both the short and long run, an elastic behavior of the German exports relative to the externai demand changes. Additionally, in the sarne period, the results corroborated the positive hypothesis of a long-term relationship between the variables. However, although the statistics and historical analysis point to the wealmess of a growth model that heavily relies on exports as a fundamental source of demand, the discussion raised forces to reflection the institutional characteristics that may actually contribute to a better understanding of the aspects that define the evolution of the recent German economic history.